1999
DOI: 10.1002/(sici)1097-0142(19990815)86:4<559::aid-cncr3>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of human telomerase catalytic subunit during gastric carcinogenesis

Abstract: BACKGROUND Telomerase activation is thought to be essential for the stabilization of telomere length, through which immortalization and oncogenesis are achieved, but little is known about the regulation of telomerase in human gastric carcinoma cells. METHODS A total of 27 primary gastric tumors, 29 cases of intestinal metaplasia, and 30 cases of normal mucosa, as well as 8 gastric carcinoma cell lines, were examined for the relation between telomerase activation and gastric carcinogenesis. Telomerase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 25 publications
2
28
0
2
Order By: Relevance
“…In addition, we also showed that HSV-1 infection can also upregulate the expression of hTERT in nontumor cells, which may cause further safety concern since upregulation of telomerase has been shown to play a critical role in carcinogenesis. 25,26 Alteration of telomerase activity has been reported in cells infected with HIV and Kaposi's sarcoma-associated herpesvirus. [35][36][37] While HSV-1/2 are not considered carcinogenic, clinical correlation between HSV-2 and human carcinoma of cervix remains to be a debatable issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also showed that HSV-1 infection can also upregulate the expression of hTERT in nontumor cells, which may cause further safety concern since upregulation of telomerase has been shown to play a critical role in carcinogenesis. 25,26 Alteration of telomerase activity has been reported in cells infected with HIV and Kaposi's sarcoma-associated herpesvirus. [35][36][37] While HSV-1/2 are not considered carcinogenic, clinical correlation between HSV-2 and human carcinoma of cervix remains to be a debatable issue.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of human telomerase reverse transcriptase (hTERT) has been shown to play a critical role in carcinogenesis 25,26 and both the hTERT gene and its promoter have higher levels of activity specifically in tumor cells. 27,28 All of these features render the hTERT promoter an attractive target for cancer gene therapy.…”
Section: Hsv-1 Upregulates Telomerase C-t Yang Et Almentioning
confidence: 99%
“…b-actin was amplified to estimate the efficiency of cDNA synthesis as described previously. 13 The PCR products were resolved on 1% agarose gels.…”
Section: Drug Treatment and Rt-pcrmentioning
confidence: 99%
“…PCR reactions were performed as follows, 951C for 5 min, and 35 cycles of 951C for 30 s, 551C for 30 s, and 721C for 30 s, followed by incubation at 721C for 10 min. b-actin was amplified, at the same time, to estimate the efficiency of cDNA synthesis as described previously (Jong et al, 1999). PCR products were resolved on 1% agarose gels.…”
Section: Drug Treatment and Rt-pcrmentioning
confidence: 99%